MINIMUM WAGES AND CONSTRUCTION WORKERS EARNING IN INDONESIA - Muhammad Iqbal Mutaqin; Choirul En Huda (Syiah Kuala University, 2021)
This study explores the impact of minimum wages on the wages of construction workers in the informal sector. Using cross-sectional data consisting of 717 samples from 62 construction projects in 24 provinces in Indonesia, we uncover that the variation of construction worker wages across provinces follows the variation of minimum wages. On the demand variables, the magnitude of GDP and workers productivity in a province is not related to construction workers' earnings. While, on the supply side, the level of formality in a province shows a positive relation to construction workers' wages. In addition, the result also supports the previous literature that the nature of construction workers is moving from one project to another across cities as part-time workers. Lastly, another finding is that the base of estimation price in public procurement for the wage of construction workers is market wage.